DAYA TARIK OBJEK WISATA AIR TERJUN HULU LEMBU DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Pitaloka, Sriona; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine: (1) To describe the tourist attraction Waterfalls Upper Calf in District Kuantan District Singingi Singingi; (2) To identify the constraints of the management of Hulu Lembu Waterfall object in the Singingi Sub-district of Kuantan Singingi Regency. This research uses qualitative method with descriptive approach, the subject of this research using the key that is, the attraction of Hulu Lembu Waterfall object, the community around the object of tourism. The data collection is done by observation, in-depth interview and document study. Data analysis used in this research that is, data reduction, data presentation and conclusion. The result of the research shows that (1) the attraction of the Hulu Lembu Waterfall object becomes a new tourist attraction which is visited by many attractions that are presented by beautiful natural scenery and the flora and fauna around waterfalls are well preserved; (2) the obstacles faced are the lack of government attention to the facilities and infrastructure of the Hulu Lembu Waterfall object, therefore it is expected that the cooperation between the people and the government in order to realize the beautiful Hulu Lembu Waterfall and is expected more and more visitors visiting the Waterfall Hulu Lembu .Keywords: Hulu Lembu Waterfall, Attractiveness